2022
DOI: 10.3390/rs14205081
|View full text |Cite
|
Sign up to set email alerts
|

Towards Forest Condition Assessment: Evaluating Small-Footprint Full-Waveform Airborne Laser Scanning Data for Deriving Forest Structural and Compositional Metrics

Abstract: Spatial data on forest structure, composition, regeneration and deadwood are required for informed assessment of forest condition and subsequent management decisions. Here, we estimate 27 forest metrics from small-footprint full-waveform airborne laser scanning (ALS) data using a random forest (RF) and automated variable selection (Boruta) approach. Modelling was conducted using leaf-off (April) and leaf-on (July) ALS data, both separately and combined. Field data from semi-natural deciduous and managed conife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 141 publications
(168 reference statements)
0
0
0
Order By: Relevance
“…This trend has also been observed in other studies using ALS systems [3,34,46,47]. Sumnall et al [48] suggested that basal area models have relatively lower R 2 values than models estimating tree height and biomass. This is likely because, unlike tree height, dbh cannot be directly measured with ALS systems.…”
Section: Discussionsupporting
confidence: 76%
“…This trend has also been observed in other studies using ALS systems [3,34,46,47]. Sumnall et al [48] suggested that basal area models have relatively lower R 2 values than models estimating tree height and biomass. This is likely because, unlike tree height, dbh cannot be directly measured with ALS systems.…”
Section: Discussionsupporting
confidence: 76%